Outcome of a public consultation on the draft update of the guidance on the use of the benchmark dose approach in risk assessment. Issue 1 (24th January 2017) - ,
Abstract : This publication is linked to the following EFSA Journal article:http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2017.4658/full